GAMBARAN TIPE KEPRIBADIAN PADA MAHASISWA PROFESI NERS: STIKes Hang Tuah Pekanbaru - Jovan Baqazarisitory Albajili; Dewi Kurnia Putri; Vella Yovinna (Jurnal Ilmu Keperawatan, 2020)
ABSTRACT Nursing Professional Practice is an advanced level for nursing bachelor students. When undergoing the Nurse profession students are required to be able to undergo various tasks given by the institution. Problems experienced by students practicing Nurse professional students in running professional practice activities and must adjust the new environment to be more familiar with the type of personality they have. The purpose of this study is to find a description of personality types in Nurse professional students. The personality has two characteristic, the chatarisic is introvert and ekstrovert. This study uses quantitative methods with descriptive research design, the population was students of Nurse Stikes profession STIKes Hang Tuah Pekanbaru with a sample of 33 people. Sampling uses a total sampling technique.Data collection tools using questionnaire and data analysis is done univariat. The results of the study were obtained that Hang Tuah Pekanbaru nurses professional 22 people (66.7%) had introvert personality type, while those 11 people (33,3%) with extrovert personality type. It can be concluded that the professional students of the Nurses STIKes Hang Tuah Pekanbaru that Introvert more than often Ekstrovert. It is expected that STIKes Hang Tuah Pekanbaru can get to know student personality type.